Residual Larvicidal Activity of Quinones against Aedes aegypti - Raquel L. Silva; Daniel P. Demarque; Renata G. Dusi; João Paulo B. Sousa; Lorena C. Albernaz; Laila S. Espindola (Molecules, 2020)
The number of documented dengue cases has increased dramatically in recent years due to transmission through the Aedes aegypti mosquito bite. Vector control remains the most effective measure to protect against this and other arboviral diseases including Zika, chikungunya and (urban) yellow fever, with an established vaccine only available for yellow fever. Although the quinone class shows potential as leading compounds for larvicide development, limited information restricts the development of optimized structures and/or formulations. Thus, in this contribution we investigated the larvicidal and pupicidal activity of three quinone compounds isolated from a Connarus suberosus root wood ethyl acetate extract together with 28 quinones from other sources. Eight quinones demonstrated larvicidal activity, of which tectoquinone (4) proved to be the most active (LC50 1.1 µg/mL). The essential residual effect parameter of four of these quinones was evaluated in laboratory trials, with tectoquinone (4) and 2-ethylanthraquinone (7) presenting the most prolonged activity. In small-scale field residual tests, tectoquinone (4) caused 100% larvae mortality over 5 days, supporting its selection for formulation trials to develop a prototype larvicide to control Ae. aegypti.